From “Local Privilege” to “Global Standard”: Facilitating Design and Copyright Protection for Non-EU Product Shapes - Annette Kur (IIC - International Review of Intellectual Property and Competition Law, 2025)
It is well known that EU law tends to offer rather generous protection for product shapes, not least under industrial design and copyright law. Until recently, however, the statement had to be qualified with regard to works or designs not originating in the EU (or the EEA). For designs, this resulted from the fact that, pursuant to the majority opinion, designs first published outside the EU were not entitled to benefit from Unregistered Community Design protection under Art. 11 of the Community Design Regulation. Concerning copyright, Art. 2(7) of the Berne Convention was assumed to bar access to protection for works that in their country of origin are only amenable to protection under industrial design law. In both aspects, recent developments in EU law have levelled the bars, turning “EU-style” protection into a “global standard”.
Keywords: 340; Design law reform; Unregistered Community designs; Supplementary unregistered design; Works of applied art; Reciprocity; Law applying to aliens